Analisis Penerapan Teori Human Becoming Rossemarie Rizzo Parse pada Anak (Dewasa-Adult) Astigmatisme - Pakpahan, Risdo; Nursanti, Irna (LPPM Institut Teknologi Dan Kesehatan Aspirasi, 2024)
Asmatigmatism is a disease that causes visual impairment at all ages, currently the author chooses it in adult children, resulting in unclear or even not sharp vision in the cornea of the eye which occurs chronically. The approaches used in treating chronic diseases are Human Becoming (Rossemarie Rizzo Parse). The methods used are case studies and literature studies. Results: Mr. Assessment with approach human becoming parse there is a problem of inadequacy structuring meaning, configuring rhythmical pattern, contrasting. The objectives set refer to the NOC based approach Human Becoming Parse. Nursing intervention, implementation and evaluation refers tonursing systemon approach Human Becoming Parse. Conclusion approach human becoming parsecan be applied to cases of ASTIGMATISM with complex complications. Nurses are expected to be able to apply assessments using a theoretical approach human becoming parsein cases of ASTIGMATISM with approach universal human becoming parse structural meaning, configuring rhythmicity pattern, trend.